Endovascular thrombectomy of acute ischemic stroke patients with systemic lupus erythematosus: two case reports - Weilong Hua; Lijun Wang; Hongye Xu; Hongyu Ma; Yongxin Zhang; Hongjian Shen; Xiaoxi Zhang; Pengfei Xing; Pengfei Yang (Future Science OA)
Patients with systemic lupus erythematosus (SLE) typically have an increased risk of thrombosis, especially at a younger age. The prognosis of those acute ischemic stroke (AIS) patients due to acute intracranial artery occlusion seems to be favorable; however, with few published reports. We report two cases of AIS that were treated with intravenous thrombolysis (IVT) and mechanical thrombectomy (MT) with a prior diagnosis of SLE and were treated with regular oral corticosteroids before the onset. During the 1-year follow-up, these two patients were able to live normally without experiencing another ischemic stroke or changing medication. SLE-associated strokes necessitate urgent attention, with prompt diagnosis and immediate therapeutic measures, including thrombolytic therapy or MT, being crucial for achieving favorable patient outcomes.